PELAKSANAAN PENGELOLAAN IKLIM SEKOLAH DALAM RANGKA MENINGKATKAN KEDISIPLINAN BELAJAR PESERTA DIDIK KELAS V DI SEKOLAH DASAR NEGERI DUREN IV KARAWANG - Ahmad Muhajir; Ferianto Ferianto (Universitas Islam Madura, 2023)
The condition or atmosphere of the school climate is something that is important to get serious attention from education implementers, because it is related to learning discipline which can be influenced by the school climate. This research aims to describe the formation of school climate towards the learning discipline of class V students at SDN IV Duren Karawang. This research uses a quantitative approach in the form of research on the influence between school climate and learning discipline. In this investigation, interviews served as the primary method of data collection. Based on the results of information analysis, it shows that the climate at SDN Duren IV is in the very good category, with a percentage of 85.01%. The learning discipline score of class V students at SDN Duren IV is in the good category with a percentage of 77.16%. There is an insignificant implementation, namely 47% of the school climate towards the learning discipline of class V students at SDN Duren IV. The level of learning discipline of class V students at SDN Duren IV increases in direct proportion to the school climate, while the level of discipline decreases in direct proportion to the school climate. The implication of this research is that education practitioners, both teachers and education personnel as well as education policy makers, can consider creating a good school climate more seriously because it can increase students' discipline in learning and seeking knowledge at school. the vision and mission of education will soon be realized, namely to educate the lives of the nation's next generation as future leaders of the nation.